Modular stimuli-responsive hydrogel sealants for early gastrointestinal leak detection and containment - Anthis, Alexandre H C; Abundo, Maria Paulene; Neuer, Anna L; Tsolaki, Elena; Rosendorf, Jachym; Rduch, Thomas; Starsich, Fabian H L; Weisse, Bernhard; Liska, Vaclav; Schlegel, Andrea A; Shapiro, Mikhail G; Herrmann, Inge K (Nature communications, 2022)
Millions of patients every year undergo gastrointestinal surgery. While often lifesaving, sutured and stapled reconnections leak in around 10% of cases. Currently, surgeons rely on the monitoring of surrogate markers and clinical symptoms, which often lack sensitivity and specificity, hence only offering late-stage detection of fully developed leaks. Here, we present a holistic solution in the form of a modular, intelligent suture support sealant patch capable of containing and detecting leaks early. The pH and/or enzyme-responsive triggerable sensing elements can be read out by point-of-need ultrasound imaging. We demonstrate reliable detection of the breaching of sutures, in as little as 3 hours in intestinal leak scenarios and 15 minutes in gastric leak conditions. This technology paves the way for next-generation suture support materials that seal and offer disambiguation in cases of anastomotic leaks based on point-of-need monitoring, without reliance on complex electronics or bulky (bio)electronic implantables.
Keywords: Early Diagnosis; Anastomotic Leak; Hydrogels; netěsnost anastomózy; Sensitivity and Specificity; senzitivita a specificita; Humans; lidé; časná diagnóza; hydrogely